Structural style & kinematic analysis of deformation in the northern Dezful Embayment, Zagros Fold-Thrust Belt, SW Iran - Joudaki, Masoud; Faghih, Ali; Mukherjee, Soumyajit; Seraj, Mohammad; Soleimany, Bahman (Marine and petroleum geology, 2024)
A comprehensive understanding of structure and kinematic characteristics of fold and thrust belts provides significant information for hydrocarbon exploration and production. The kinematic evolution and structural style of three subsurface oilfields, Zeloi, Lali and Karun, in the northern part of the Dezful Embayment, a significant petroleum province of the Zagros Fold-Thrust Belt in SW Iran, were investigated using 2D seismic data. Interpretation of the 2D seismic profiles with up to 5 km depth consisting of upper Jurassic to Pleistocene sediments and the balanced cross-sections constructed revealed diverse geometries and kinematics along the oilfields. These results demonstrate that the structural style of the oilfields was controlled by the Gachsaran and Dashtak formations as upper and middle detachment levels, respectively. Tear faults affected the along-strike variations in structural style of the oilfields. Based on the analysis of growth strata, folding evolved as limbs rotated and hinges migrated, beginning in the mid-Miocene. During the later stages of deformation, the initial detachment folds transformed into fault-bend folds. •The kinematic evolution and structural style of subsurface oilfields, Zeloi, Lali and Karun.•The structural style of the oilfields was controlled by several detachment levels.•The tear faults affected the along-strike variations in structural style of the oilfields.•Understanding of kinematics of folds provide information for hydrocarbon exploration.